Yield and Quality of Two Cultivars of Sugar Beet as Influenced by Fertilizer Applications (Biological Sciences - PJSIR, 2006)
Studies were conducted to determine the effect of different doses of nitrogen and phosphorous applications on the yield and quality of two varieties of sugar beet. The genotypic varieties included in the study were: USH-10 and Maribo Extrapoli. Fertilizer doses applied were: 56.2, 113.7 and 170.0 (kg/ha) each of N and P. Results indicated that at the same leavel of fertilizer application, the two varieties did not differ significantly in root yield (kg/ha), sugar contents (%) and sugar yield (kg/ha). Yield, however, was significantly (p < 0.01) influenced by the application of different doses of N and P. The yield was the lowest for control (zero fertilizer application), and increased (p > 0.01) with the first two fertilizer doses. However, a decline in the yield (p < 0.01) was noted with the further higher dose of fertilizers. Sugar contents as percent yield did not differ in the two varieties. Fertilizer application resulted in signifi- cantly (p < 001) higher sugar level only upto the second dose. The results revealed that the second dose (113.7 : 113.7 kg/h of N : P) was the most economical level of fertilizer application for sugar beet crop cultivation in the agro-climatic region of Peshawar, Pakistan.